Subtract. Express your answer as a polynomial in standard form.

(8x^3−4x^2+9x+8) − (6x^2−7x+8)=

1 answer

To subtract the polynomials, we need to subtract each term separately.

(8x^3 - 4x^2 + 9x + 8) - (6x^2 - 7x + 8)

First, let's subtract the x^3 term:
8x^3 - 6x^2 = 2x^3

Next, subtract the x^2 term:
4x^2 - (-6x^2) = 4x^2 + 6x^2 = 10x^2

Next, subtract the x term:
9x - (-7x) = 9x + 7x = 16x

Finally, subtract the constant term:
8 - 8 = 0

Putting it all together, we have:

2x^3 + 10x^2 + 16x + 0

Simplifying further, we have:

2x^3 + 10x^2 + 16x
Similar Questions
    1. answers icon 1 answer
  1. Given: f(x)=2x^2+x-3 and g(x)=x-1Express: f(x)⋅g(x)-[f(x)+g(x)] as a polynomial in standard form
    1. answers icon 1 answer
  2. PLS HELP ME!!I really need the answers to these few questions I need toturn them in ASAP. Simplify each polynomial. Write each
    1. answers icon 2 answers
    1. answers icon 7 answers
more similar questions